Clinical characteristics, gestational weight gain and pregnancy outcomes in women with a history of gestational diabetes mellitus - Liang, Xin (Diabetol Metab Syndr, 2021)
BACKGROUND: Pregnant women with a history of gestational diabetes mellitus (GDM) are at high risk of GDM. It is unclear whether this population has pregnancy characteristics different from the general population. Whether these features affect the perinatal outcome has not yet been elucidated. METHODS: A retrospective study was conducted, including baseline characteristics, laboratory data, gestational weight gain (GWG), and pregnancy outcomes of 441 pregnant women with prior GDM. Besides, 1637 women without a history of GDM treated in the same period were randomly selected as the control group. The above indicators of the two groups were compared. Multivariable logistic regression analysis was performed to investigate how GWG was associated with perinatal outcomes for previous GDM women. RESULTS: Among women with GDM history, triglycerides (TG) and fasting plasma glucose (FPG) in the 1st trimester were higher than those without GDM history. GWG was lower in women with prior GDM relative to the control group at various pregnancy stages. However, women with GDM history had a higher risk of developing GDM (OR 3.25, 95% CI 2.26–4.68) and pregnancy-induced hypertension (OR 1.50, 95% CI 1.05–2.45). In women with previous GDM, excessive GWG before OGTT exhibited a positive correlation with pregnancy-induced hypertension (OR 1.47, 95% CI 1.05–3.32), while inadequate GWG was not a protective factor for GDM and pregnancy-induced hypertension. CONCLUSION: Women with prior GDM have glucose and lipid metabolism disorders in the 1st trimester. Limited reduction of GWG before oral glucose tolerance test (OGTT) was insufficient to offset the adverse effects of glucose and lipid metabolism disorders in women with previous GDM. Relevant interventions may be required at early stage or even before pregnancy.